What Teachers Do Before They Teach: Lesson Preparation Practices Of EFL Teachers In An Indonesian High School - Rusdin, Maryam; Fakhruddin, Zulfah; Tjalla, Magdahalena; Kalsum, Kalsum (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Lesson preparation is an essential aspect of effective teaching because it enables teachers to organize instructional strategies, teaching materials, and learning resources to achieve educational objectives. However, limited studies have explored how these components are integrated simultaneously in teachers’ lesson preparation practices within EFL contexts. Therefore, this study aimed to investigate how English teachers prepare classroom instruction, integrate instructional strategies, teaching materials, and technology, and address the challenges encountered during the preparation process. This qualitative case study was conducted at SMA Negeri 6 Sidrap and involved three English teachers selected through purposive sampling. Data were collected through semi-structured interviews and analysed using thematic analysis proposed by Braun and Clarke (2006). The findings revealed that teachers prepared classroom instruction through flexible and contextual lesson planning by adapting instructional strategies, teaching materials, and classroom activities to students’ needs and classroom conditions. Teachers also integrated technology such as YouTube, LCD projectors, Smart TVs, and internet-based resources to support learning. However, the integration of instructional strategies, teaching materials, and technology remained limited and inconsistent because these components were often implemented separately rather than systematically integrated into a cohesive instructional design. In addition, teachers encountered several challenges, including unstable internet connectivity, diverse student abilities, classroom management issues, and limited preparation time. The study concludes that lesson preparation is an adaptive pedagogical process influenced by classroom realities, teachers’ competence, and institutional support. These findings highlight the importance of continuous professional development and stronger support for technology integration to enhance lesson preparation practices in EFL classrooms.